Interview with Jack Halberstam: Anarchitecture, intergenerational tensions and non-binary structures of desire: gender as a field of struggle - Fuenzalida, Fede; Falabella, Soledad (Nomadías, 2025)
“Non-binary is a big “NO” that is expressed through gender, and this has profound political implications. I have no idea how the concept will develop in the future, but I know that if I were young, my animosity would be directed against those who have ruined everything for me.” The book Feminine Masculinity, published in 1998 by Jack Halberstam, marked the beginning of a summer of intensive reading about his work. A message of admiration through a social network unexpectedly led to an interview with the author. Below, we share a fragment of our conversation, which took place one afternoon in June 2024, during his visit to Chile.